(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
Neutron radiography is a powerful non-destructive testing (NDT) technique for internal evaluation of materials, such as voids/cavity, cracks, homogeneity, water absorption behavior, etc. It involves attenuation of a neutron beam by an object to be radiographed and thus to make the registration of the attenuation process (as an image) on a film or video. In the present investigation neutron radiography (NR) imaging technique has been adopted to study the quality like homogeneity, porosity, water penetrating height, behavior of incremental intrusion area, initial rapid absorption (IRA) of the brick-DK sample. Thermal neutron radiography facility installed at the tangential beam port of 3MW TRIGA MARK-II reactor is used in this study. In this cases optical density or gray values of the neutron radiographic images of the sample is measured. From this measurement it is found that the contents of the sample is not uniformly distributed all over the sample which indicates the presence of large number of internal porosity, at the two edges water uptake is slightly poorer than the middle part and initial rapid absorption is very high. Water penetrating inside the sample is faster. The results obtained and conclusion made in this study can only be compared to the properties of bricks produced under similar conditions with similar raw materials. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18273 Bangladesh J. Sci. Ind. Res. 48(4), 237-246, 2013